The Nuremberg legacy : how the Nazi war crimes trials changed the course of history - Ehrenfreund, Norbert 1921- (Palgrave Macmillan, 2007)
"Norbert Ehrenfreund draws from his experience as a correspondent for The Stars and Stripes during the Nuremberg trials to deliver a fresh analysis of the precedents set there. Skillfully employing his legal background as a judge for the Superior Court of California, Ehrenfreund discusses contemporary courts' interpretations of Nuremberg legal doctrines and their effects on national and international law today. He reveals how the precedents set at Nuremberg continue to play a role in our daily lives, affecting human rights, race relations, medical practice, big business, and the modern war crimes trials of tyrants like Slobodan Milosevic and Saddam Hussein."--BOOK JACKET.